Digital Class-D amplifier - Su, Liwei (2016)
In today’s audio power amplifier industry, the Class-D amplifier is extremely prevalent concept because of its high power efficiency and small size. A typical Class-D amplifier is made of three stages: a pulse width (PWM) modulator stage, an output power stage and an inductor-capacitor (LC) low pass filter stage. With the development of digital signal processing and digital storage technology, the PWM modulator or feedback controller can be constructed using digital methods, to yield a fully digital Class-D amplifier. In this dissertation, an open-loop single-end Class-D power amplifier is first designed and simulated using Cadence simulation tool, and based on Global Foundries 0.18um CMOS technology. Then, a feedback digital Proportion Integration Differentiation (PID) controller is designed and simulated using MATLAB, to equip the designed Class-D amplifier so as to reduce the noise and to ensure stability of the circuit. In all, this dissertation proposed a novel Class-D amplifier with digital PID controller to drive an 8-Ohm speaker. The efficiency of this Class-D amplifier is high and the total harmonics distortion (THD) is less than 0.5% at 10 kHz.